Effectiveness of Palliative Care in Heart Failure Patients in Preventing Readmission: A Systematic Review - Osty Histry Kapahang; Dewi Gayatri; Tuti Herawati (NurseLine Journal, 2023)
Palliative care is an essential part of the management of heart failure patients. By integrating palliative care in treating heart failure patients, patients experience calm and feel a safe atmosphere both physically and psychosocially, and with other problems, and make patients have the same understanding from a medical perspective. To summarize the results of studies related to palliative care in heart failure patients and to identify specific and effective practices in preventing readmission. Systematic search of the PubMed, Science Direct, and ProQuest databases searching for articles that included heart failure and palliative care. Palliative care is a critical component of health care for heart failure patients. In this article, the authors summarize the effectiveness of patient-focused palliative care and the palliative team in preventing readmissions and improving patients' quality of life when palliative care is applied in health care. Implementing palliative care in patients with heart failure is highly recommended for enhancing the patient's quality of life (QoL) and preventing or reducing patient readmission rates if appropriately implemented. Focusing on improving the abilities and skills of the palliative team is also something that needs to be considered. Also, knowledge, understanding, and involvement of the patient's family in patient care at home are significant.